Avenue de la liberté - Fiorentino, Julien (France, 2010)
After having worked as a coordinator of the Cultural Insertion Course around SPIP 94, a cultural reintegration program for people detained in one of the toughest prisons in France. The film links the conditions of detention in Fresnes and the quality of the cultural projects that take place there, and the detainees and artists, judges and staff, testify to this extraordinary human adventure.
Verzio Film Festival Submission
Keywords: Documentary films